1999
DOI: 10.1164/ajrccm.160.1.9809024
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Prolonged Chloroquine Therapy in Advanced Pulmonary Sarcoidosis

Abstract: Sarcoidosis may cause severe ventilatory impairment requiring corticosteroid treatment. Chloroquine (CQ) can be an effective treatment for lung sarcoidosis with few side effects, but has not been accepted as standard therapy. We investigated the benefits of prolonged CQ therapy in 23 symptomatic patients with biopsy-proven pulmonary sarcoidosis (duration, >/= 2 yr). Patients were initially treated for 6 mo with CQ, 750 mg/d, tapering every 2 mo to 250 mg/d. Eighteen patients were then randomized to either a Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 22 publications
1
73
0
10
Order By: Relevance
“…Two randomized controlled trials demonstrated the role of chloroquine in the treatment of sarcoidosis [16,17]. The first one from 1967 showed significant improvement on dyspnea scores, pulmonary function and radiographic abnormalities by 6 months in the chloroquine group.…”
Section: Antimalarial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two randomized controlled trials demonstrated the role of chloroquine in the treatment of sarcoidosis [16,17]. The first one from 1967 showed significant improvement on dyspnea scores, pulmonary function and radiographic abnormalities by 6 months in the chloroquine group.…”
Section: Antimalarial Agentsmentioning
confidence: 99%
“…By 12 months, there was no difference between the groups, partially because of recurrence of disease after discontinuation of chloroquine [16]. A subsequent small trial concluded that keeping patients on a lower maintenance dose of chloroquine caused a slower decline of lung function compared to placebo [17]. The antimalarials (mainly the less toxic but less potent relative hydroxychloroquine) are primarily used in patients with skin and joint manifestations, as well as hypercalcemia.…”
Section: Antimalarial Agentsmentioning
confidence: 99%
“…Hydroxychloroquine has shown less toxicity than chloroquine; however, chloroquine appears to be more effective. With only limited or small trial results available the true efficacy of antimalarials has not fully been determined; however, they have shown effectiveness in cutaneous and pulmonary sarcoidosis [118,119].…”
Section: Antimalarialsmentioning
confidence: 99%
“…Some studies also exist in which these drugs have been used to treat pulmonary sarcoidosis (Chloroquine in pulmonary sarcoidosis, 1968). Bazan et al (Baltzan et al, 1999) studied the use of chloroquine to treat chronic sarcoidosis. After treating 18 patients for 6 months, treatment was continued with a group of patients with a slower decrease in FEV1 and diffusion capacity, but no changes in forced vital capacity were registered, although important adverse effects were produced in 13% of cases.…”
Section: Antimalarial Agents 251 Chloroquine and Hydroxychloroquinementioning
confidence: 99%